Student feedback towards educator performance in technical college: a case study in KKTMSG Johor Malaysia - Yusof, Yusliandy; Mohd Salleh, Kahirol; Che Him, Norziha (2020)
Student feedback is one of the important component in the learning and teaching process evaluation at various stages of higher level education in Malaysia. Kolej Kemahiran Tinggi MARA Sri Gading (KKTMSG) with eight departments is a location of study that have intakes twice a year, January-June (JJ) and July-December (JD). A continuous assessment by student has been executed over years and compulsory to fill in during the final examination week around May and November. Four objectives of this study are to determine if there is any correlation exist be-tween Educator Mark with Total Marks of Personality and Teaching and Learning, to investigate if there is any correlation exist between Person-ality and its criteria, to explore if there is any correlation exist between Teaching and Learning and its each criteria and finally to determine if any association exist between Gender and Educator Mark with hypothesis null that both variables are independent. Main instrument used is a ques-tionnaire with quantitative research design survey technique consists of basic Demography, Personality and Teaching and Learning sections. The survey question is in a Likert scale start from 1 to 5 that represent Never, Almost Never, Sometimes, Almost Every Time and Every Time respectively. The dependent variable is an Educator Mark meanwhile the independent variables consists of 24 variables known as Semester, Year, Educator, Gender, Department, Student, 20 variables of criteria selection from Personality with 8 questions and from Teaching and Learn-ing with 12 questions in a Likert scale. Descriptive analysis, correlation analysis and chi-square test have been adopted to this study. Result shows that 55.4% and 44.6% of the sample data are male and female respectively, which sounds reasonable represent the population of educa-tor in KKTMSG and the highest respondent for both genders represent from PA Department. First objective presents a strong relationship with correlation value at 0.976 for Teaching and Learning compared to Personality and second objective shows all criteria have strong relationship with criteria Fairness, E presents highest correlation value at 0.976 compared to others. In the meantime, third objective 3 display similar result that criteria Committed During Teaching and Learning Process, T represents highest correlation value at 0.984 compared to others. All these results were based on significant p-value of less than 0.05. Finally, a Chi-Square Test conclude that Gender and Educator Mark are independent, and this shows that students are freely to evaluate educator in KKTMSG without consider or concern either the educator is male or female.